The Condition of Companies and their Growth Based on the Example of Companies Included in WIG and DAX Indices - Bolek, Monika; Gniadkowska-Szymańska, Agata (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis: The paper discusses the problem of condition of companies together with their growth measured by earnings per share, sales, assets and equity. The condition of a company in a capital market is considered good when the goal of the business is achieved, namely the increase of value that occurs with the increase of earnings per share. We assume that the condition of companies measured by Altman’s Z-score Model scores is related to their growth, and ratios applied in this model influence the growth of companies measured by EPS, sales, assets and equity. The research is conducted in two groups of companies, one representing WIG listed entities and the other one comprising DAX listed companies.Methodology: The growth of earnings per share is considered as a measure of companies’ value creation. The growth of EPS should be related to the growth of sales, assets and equity according to the growth theory. To analyze the influence of Altman’s Z-score Model on the growth of EPS, sales, assets and equity, the Pearson and Spearman correlation is applied in the first place. Moreover, logit models are applied to analyze the influence of ratios composing the Altman’s Z-score Model on the growth of EPS, sales, assets and equity.Results of the research: Discriminant models can be applied for the assessment of the economic condition of companies but the interpretation of the results should take into account the fact that risky strategies identified by Altman’s Z-score Model as dangerous are related to the higher growth of earnings per share, therefore, there should be a negative relationship between Altman’s Z-score Model scores and EPS growth and it was confirmed in this study.